Effective delivery of osteopontin small interference RNA using exosomes suppresses liver fibrosis via TGF-β1 signaling - Tang, Min; Guo, Cheng; Sun, Mengxue; Zhou, Hao; Peng, Xin; Dai, Jianli; Ding, Qin; Wang, Ying; Yang, Changqing (Frontiers in Pharmacology, 2022)
Objective and aims: Osteopontin (OPN), a matrix-bound protein sensitive to oxidant stress, plays a central role in liver fibrosis. While OPN expression can be reduced by small interfering RNA (siRNA), the challenge to deliver siRNA safely and effectively into liver remains unresolved. Exosomes are promising natural nanovectors for drug delivery with capacity to efficiently enter cells across different biological barriers. Here, we utilize exosomes as delivery conduit to target OPN in liver fibrosis. Methods: Exosomes selectively home to fibrotic liver according to small animal imaging system. Electroporation technique was used to engineer exosomes to carry siRNA targeting OPN (ExosiRNA-OPN). Primary hepatic stellate cells (HSCs) was isolated and treated with ExosiRNA-OPN to assess the effect on activated HSCs (aHSCs). Immunofluorescence for α-SMA, an aHSCs marker, and sirius red staining were performed to assess ECM deposition. Finally, plasma OPN from patients with liver fibrosis was identified by ELISA assay. Results: Exosome-mediated delivery of siRNA showed high uptake and low toxicity. Besides, ExosiRNA-OPN suppressed HSCs activation and ECM deposition and restored liver function more efficiently compared to naked siRNA-OPN. Moreover, ExosiRNA-OPN was assumed inhibiting TGF-β1 signaling activation, along with other fibrotic-related genes based on a GEO datasheet of liver fibrosis samples for correlation analyzes. ExosiRNA-OPN inhibited TGF-β1 signaling by decreasing high-mobility group box-1 (HMGB1). Plasma proteins from chronic HBV-induced fibrosis patients were identified that patients with high OPN expression correlates with more advanced fibrosis progression. Discussion: The present study demonstrates exosome-mediated siRNA-OPN delivery may be an effective treatment option for liver fibrosis.